Increased parental history of bipolar disorder in the United States: association with early age of onset. (19th October 2013) - Post, R. M.; Leverich, G. S.; Kupka, R.; Keck, P.; McElroy, S.; Altshuler, L.; Frye, M. A.; Luckenbaugh, D. A.; Rowe, M.; Grunze, H.; Suppes, T.; Nolen, W. A.
<x xml:space="preserve">Abstract</x> Objective Early‐onset bipolar (BP) disorder and other poor prognosis characteristics are more prevalent in patients from the United States than from the Netherlands and Germany (abbreviated as Europe). We explored the impact of parental loading for affective illness on onset and other characteristics of BP disorder. Method Parental history for unipolar (UP) and bipolar (BP) depression and course of illness characteristics were obtained from self‐report in adults (average age 42) with BP disorder. Illness characteristics were examined by χ2 and multinomial logistic regression in relationship to the degree of parental loading: i) both parents negative; ii) one UP disorder; iii) one with BP disorder; and iv) both affected. Results After controlling for many poor prognosis factors, compared with those from Europe, patients from the United States had more iii) one parent with BP disorder and iv) both parents affected. An early age of onset of BP disorder was independently associated with this increased parental loading for affective disorder. Conclusion Parental history of BP disorder and both parents with a mood disorder were more common in the United States than Europe and were associated with an early onset of bipolar disorder and other poor prognosis characteristics. These findings deserve replication and exploration of the potential mechanisms involved and their therapeutic implications.